UM OLHAR A PARTIR DE ATOS DE FALA DO ROMANCE VIDAS SECAS - Moraes, Marcela Marabeli de (2015)
This thesis has the general objective to reflect about some aspects of the language policy that can permeates the speech acts (Armengaud, 2006; Melo, 2014; Ottoni, 1998; Pinto, 2006, 2014) of the novel Vidas secas (Candido, 2012; Moraes, 2012) written by Graciliano Ramos, in order to improve the approaches which refers to language policy (Correa, 2014; Rajagopalan, 2013, 2014) and agencies (Asad, 2000; Ahearn, 2000) from one study proposal of one classic book of the national literature. As the hypothesis of this work, we comprehend that, as the characters discover the language during the narrative, we, as readers and researchers of the work, (re)discover other linguistics resolutions, which are reiterated by the speech acts of the migrants family. To develop this idea, the methodological procedures interleave theoretical research and the analysis of the related work, which features the corpus of this work. In this sense, the research is divided in three axis: linguistics policies, speech acts and the literary text in question, which are interconnected by the mean of specifics objectives: a) discuss the concepts of policy and linguistics politics; b) investigate possible traces of linguistics policy in the literary writing of Graciliano Ramos; c) know the author´s political identity; d) Defend the idea that Vidas secas corresponds to one novel about the language discovery; e) think about the speech acts and the political function of them in this narrative; f) define the characters as social agents and their practice as agencies. As the research results, we comprehend that the “language has, in addition to everything that is believed that it has, one political dimension” (RAJAGOPALAN, 2014) in an emancipatory research or not. This way, we see Fabiano, Sinhá Vitória, Menino mais velho e Menino mais novo as linguistics agents, managers of agencies supported in the critical resolution, especially, related to the power and the hegemonic speech, turning them into agents in civilization process, essentially, by the capacity of auto knowledge and social knowledge of them. We emphasize that the present study is a part of the Works for the Ponta Grossa State University Master Program in Language, Identity and Subjectivity.